Effectiveness of Automatic Feeder in Catfish Cultivation (Clarias gariepinus) with Biofloc System - Alfajri Yuda Permana; Ayu Putu Wiweka Krisna Dewi; Gde Raka Angga Kartika (Advances in Tropical Biodiversity and Environmental Sciences, 2024)
Catfish is a popular fish species in the community and is cultivated by many people. Catfish are considered superior to other freshwater fish. One system that can improve catfish quality and ability is the biofloc system. Biofloc system is considered more effective compared to other systems because it increases the productivity of cultivated fish. Unfortunately, cultivation in general is considered a traditional system that only uses manpower to do all activities such as feeding. One application of feeding technology is automated feeding machines. This research is aimed to determine the effectiveness of the automatic feeder on catfish cultivation with biofloc system. The research method was experimental and compared 2 treatments, which were A (biofloc without an automatic feeder) and B (biofloc with an automatic feeder). Fish samples used were 5-7 cm in size and reared for 44 days at the cultivation pond of Marine and Fisheries Faculty, Udayana University. The results of this research are SGR, FCR, and SR. Based on the results, treatment B had better SGR (3.37%), FCR (2.03) and SR (45%) compared to treatment A. The conclusion of this research is the usage of automatic feeder in catfish cultivation with biofloc system has better results than without the usage of automatic feeder.